Quality of life and needs of persons with acquired brain injury 3 to 5 years after completion of coordinated rehabilitation - Kuželková, Anna; Vacková, Jitka; Bendová, Markéta; Jirků, Anna; Pechoušková, Kateřina; Mandátová, Kateřina (Journal of nursing, social studies and public health, 2024)
Objectives: The article points out the importance of coordinated rehabilitation in the personal social environment of people with acquired brain injury (ABI) after discharge from the treating medical facility. We compared the client’s/patient’s subjective perception of their quality of life and special needs several years after ABI to those same items immediately after the coordinated rehabilitation period. Methods: The research was designed as a qualitative pilot study with auxiliary quantitative indicators. It was a longitudinal six-year study, concluded in April 2021 with a computer- assisted telephone interview (CATI) to determine the status and needs of participants. There were 17 client/patient participants. Results: Research suggests that if therapy after ABI is not continued, clients/patients often reverse the gains made during 3-month coordinated interventions and, according to WHODAS 2.0, can return to pre-intervention levels within a year. Three or more years after ABI, clients/ patients subjectively perceive that improvement in their condition has stagnated or has only slightly improved, and most reported a deterioration in their quality of life. Conclusion: While participants were coping with their ABI, it was clear that long-term follow-up involving rehabilitation or at least longer-term professional help and support was desperately needed to help clients/patients maintain their initial improvements.